ANALISIS KESALAHAN FONOLOGI DALAM KETERAMPILAN BERBICARA BAHASA ARAB DI PONDOK PESANTREN PUTRI DAARUL FIKRI MALANG - Mabruroh, Nasikhatul; Hikmah, Khizanatul (Jurnal Dedikasi Pendidikan, 2024)
This research focuses on the analysis of phonological errors in Arabic speaking abilities at the Daarul Fikri Malang Islamic Boarding School for Girls. The research method applied is qualitative descriptive, meaning that the search for facts is conducted through the interpretation of the data found, with the approach being a language error analysis approach to identify and elaborate on the phonological errors that arise in the mastery of speaking Arabic at the Daarul Fikri Malang Islamic Boarding School for Girls. In this research, the researcher used data collection techniques such as observation, documentation, and interviews. The analysis results indicate that 1.) Some types of phonological errors such as a. letter substitution b. letter addition c. letter deletion. 2.) The causes of phonological errors are a. language interference b. differences in phonological systems c. differences in educational backgrounds d. lack of practice in speaking Arabic. 3.) Proposed solutions include a. ishlahul lughoh for language correction b. and the provision of special intensive classes for learning ashwat using phonetic methods and mim-mem methods to improve speaking skills.